Kala Sungsang: Recording World Voices to Draw Creative Innovations in a New Normal Era - Sahid Teguh Widodo (Javanologi: International Journal of Javanese Studies, 2023)
Kala Sungsang is a term in Javanese which marks a situation where a major disaster has occurred and turned the situation upside down. The big disaster in the Javanese language itself is named by the term pageblug. That is how the Javanese people describe the covid-19 pandemic disaster that is still happening today. The form of this research is qualitative research which is considered appropriate to find a way out of dealing with a pandemic by recording the voices of the world from cultural experts around the world. Data were collected from eight informants from Indonesia, the Netherlands, Japan, India, England, America and Australia. The data analysis technique uses an interactive analysis model, by means of grouping and interpreting it carefully and thoroughly. The results showed that there was a similarity in opinion of each informant, with regard to future values and expectations. The dominant values that emerge are togetherness, persistence, improving on communication, self-strengthening, keep looking and generating new ideas, finding solutions, and always think positively. This research shows the determination and desire of world citizens to dare to face and help each other in handling the Covid-19 pandemic.